Interstitial lung disease, a common manifestation of newly diagnosed polymyositis and dermatomyositis. Issue 3 (12th February 2004) - Fathi, M; Dastmalchi, M; Rasmussen, E; Lundberg, I E; Tornling, G
Abstract : Objectives: To estimate the prevalence and predictors of interstitial lung disease in newly diagnosed polymyositis and dermatomyositis. Methods: A prospective study in which consecutive patients with newly diagnosed poly- and dermatomyositis, regardless of clinical symptoms of pulmonary disease, were investigated with chest x ray, high resolution computed tomography (HRCT), pulmonary function tests, and biochemical and autoantibody analysis. Patients with inclusion body myositis, malignancy, other defined inflammatory connective tissue diseases (CTDs), or antibody profile indicating other CTDs were excluded. Results: Between March 1998 and September 2000, 26 new cases of poly- or dermatomyositis were diagnosed; 17 of those patients were included in the study. Interstitial lung disease (ILD), defined as radiological signs on chest x ray examination/HRCT or restrictive ventilatory defect, were found in 11 (65%) patients and were more common in men than in women. Arthritis and occurrence of anti-Jo-1 antibodies were found more often in patients with ILD than in those without. There was no statistically significant association between respiratory symptoms, other serological or laboratory variables and ILD. Conclusions: ILD is a common early manifestation in patients with poly- and dermatomyositis and is not always related to clinical symptoms. Chest x ray examination, HRCT, pulmonary function tests, and analysis of anti-Jo-1 antibodies should be included in the initial investigation of patients with myositis regardless of respiratory symptoms.